Place, policy and pedagogy: a literacy ethnography of a small town - Smith, Helen Victoria (2019)
At a time when getting the ‘best start’ in early childhood is seen as essential for ‘school readiness’, educational attainment and economic success, the thesis considers how resources in an East Midlands' town are used by mothers to support their young (under 5) children's literacy development. The study adopts an ethnographic approach and relates to other place-based literacy research such as that carried out by David Barton & Mary Hamilton and Shirley Brice-Heath. Drawing on Bernstein’s ideas of visible and invisible pedagogies, the study investigates how English education policy is interpreted and enacted through the different literacy resources that are made available to different communities within the town. The findings reveal the ways in which mothers are 'taught' to support their young children's literacy development differently depending on how they are framed, where they live and where they go. Additionally, Bourdieu’s concepts of capital and habitus help to shed light on the different ways mothers support their children’s literacy development and how they view their own and others’ role. It is argued that the adoption of particular pedagogies and practices in different places within the town give mothers mixed messages, reinforce deficit discourses and perpetuate educational inequalities.